Stroke Severity and Constipation in Ischemic Stroke Patient in Indonesian Regional Hospital - Azham Purwandhono; Satria Arju Ridho Robby; Kristianningrum Dian Sofiana; Muhammad Ihwan Narwanto; Novan Krisno Adji (Faculty of Medicine, Universitas Padjadjaran, 2026)
Ischemic stroke can lead to a range of complications, incluing constipation. This study aimed to evaluate the relationship between stroke severity history and constipation among ischemic stroke patients treated at the Outpatient Neurology Clinic of dr. Soebandi Jember Regional Hospital. This cross-sectional observational analytic study was conducted on 37 first-attack ischemic stroke patients who met the inclusion and exclusion criteria during the period of June to November 2024. Stroke severity data were obtained from medical records using the National Institutes of Health Stroke Scale (NIHSS) score. Meanwhile, constipation incidence data were obtained through interviews using the Constipation Scoring System (CSS) questionnaire. Data collected were then analyzed using the Spearman test. Most subjects were ≥60 years (39.5%), male (62.2%), and graduated from elementary school (45.9%). Most patients had moderate stroke severity (40.5%) and moderate constipation (40.5%). There was a significant relationship between stroke severity and constipation (p=0.001) with a strong correlation strength (r=0.524) and a positive correlation direction. In conclusion, stroke severity has a strong, directly proportional relationship with constipation in ischemic stroke patients.